Increase in oil extractability of coconut residue using active cultures of Trichordema viride (Trichoderma reesei) - Duran, Ma. Sailannee (1990)
ABSTRACT The main purpose was to effect an increase in the extractability of the oil in coconut residue ("sapal)" using the procedure from the protein-enrichment of the same raw material. Nutrients were added to "sapal" on a 90:1 carbon to nitrogen ratio, "sapal" being the sole carbon source. All substrates were pH adjusted to 4.5 and were sterilized before the actual fermentation run. Comparison of the amount of oil extracted before (control) and after fermentation were done to ascertain the increment increase in oil extractability. Phase I (determination of duration of fermentation) data gathered after four, six and eight days, showed that the last gave the highest increase in oil extractability (28.1% = 65.7% - 37.6%, for batch 1 and 25.5% = 63.5% - 38.0% for batch 2). Eight days was then adopted in phase II (determination of substrate to water ratio) where data for 1:1, 1:3, and 1:5 substrate-water ratios revealed the highest increase for the last (22.7% = 60.3% - 37.6% for batch 1 and 23.9% = 61.9% - 38.0% for batch 2). Statistical analysis affirmed the significant effects of the variables studied.